Agminated Flexural Melanocytic Nevi: A Late Sequela of Langerhans Cell Histiocytosis?. Issue 3 (17th March 2015) - Feldstein, Stephanie; Funk, Tracy; Smith, John C.; Bruckner, Anna L.
Abstract Agminated flexural melanocytic nevi in children with a history of Langerhans cell histiocytosis (LCH) are rare and thought to be coincidental or related to systemic chemotherapy. We report on an 11‐year‐old boy in remission from LCH, treated with only topical steroids, who presented years later with an eruption of melanocytic nevi in the bilateral inguinal and axillary regions. Rather than coincidence, we hypothesize that agminated flexural melanocytic nevi are a late sequela of LCH, possibly resulting from immune tolerance or a reaction to local inflammation.